Carducci editor: the collaboration with Gaspero Barbèra’s «Diamante» (Prassi Ecdotiche della Modernità Letteraria, 2022)
The paper focuses on the ways and results of the almost twenty-year collaboration of Giosuè Carducci to Gaspero Barbèra’s «Collezione Diamante» (1858-1874), also with the support of the correspondence (the 186 letters of Barbèra, almost totally unpublished, are in Bologna, at Casa Carducci). Particular attention is paid to Carducci’s role in defining the «Diamante», of which he was the responsible of the poetic section (since 1860). Three are the issues at the center of this reflection: the criteria that guided the choice of authors and works; the ecdotic method of Carducci; the educational purpose of a project, that aimed to establish a literary canon for the public of the newborn Italy.
Keywords: Giosuè Carducci; Gaspero Barbèra; Diamante; Italian Unification; literary canon; editorial method